Gugatan Lain-Lain oleh Kurator sebagai Instrumen Perlindungan Hukum Kreditur atas Pertanggungjawaban Pribadi Direksi dan Komisaris dalam Kepailitan Perseroan Terbatas : Studi Putusan Nomor 706 K/Pdt.SusPailit/2021 - Callista Ottodinata; Eko Yudhistira Yudhistira; Syarifah Lisa Andriati (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The principle of limited liability in a limited liability company is not absolute, as it can be pierced through the piercing the corporate veil doctrine when directors and commissioners are proven to have breached their fiduciary duty, causing the company to become bankrupt with insufficient bankruptcy estate to settle all obligations to creditors. This study examines the legal standing of the curator in filing ancillary lawsuits and the mechanism of applying the doctrine as the basis for personal liability of corporate organs, analyzing Supreme Court Decision Number 706 K/Pdt.Sus-Pailit/2021. A normative juridical method was employed with statutory, conceptual and case approaches. The results show that the curator holds a strong legal mandate to file ancillary lawsuits upon finding indications of organ negligence causing estate insufficiency. The doctrine is applied proportionally through cumulative evidentiary elements with a reversed burden of proof.